Modelling chemistry and transport in urban street canyons: Comparing offline multi-box models with large-eddy simulation. (1st November 2021) - Dai, Yuqing; Cai, Xiaoming; Zhong, Jian; MacKenzie, A. Rob
Abstract: Computational fluid dynamics models are resource-intensive, particularly when complex chemical schemes are implemented, and this computational expense limits their use in sensitivity analyses. We propose a flexible multi-box model that permits spatial disaggregation of sources and depositions to simulate the transportation and distribution of chemical species in street canyons with any aspect ratios for which a large eddy simulation (LES) of the flow exists. The spatial patterns of reactive species in the multi-box simulations are in good agreement with those from the LES, especially for the deep canyon from which air escapes more slowly. The overestimation of the LES simulation worsens somewhat due to segregations when the chemistry of volatile organic compounds (VOCs) is included but the overall pattern is captured in a modelling framework. By reducing computational costs by several orders of magnitude, the multi-box model allows more sensitivity testing than the LES, and is an effective approach to investigate spatial pattern of fast non-linear chemistry or microphysics at the street scale. Graphical abstract: Image 1 Highlights: NOx -O3 -VOC chemical reactions are coupled with multi-box canyon models. The multi-box models reproduce flow characteristics in regular and deep canyons. Reactive species concentrations in street canyons are well captured in <1% of the run time of computational fluid dynamics. The impacts of segregation on reactive species can be investigated.